Assessing potential impacts of phosphate precipitation on nitrous oxide emissions and the carbon footprint of wastewater treatment plants. Issue 16 (16th July 2019) - Kosse, Pascal; Lübken, Manfred; Schmidt, Torsten C.; Lange, Ruben-Laurids; Wichern, Marc
ABSTRACT: Metal salts are widely used for the precipitation of phosphorus during wastewater treatment transforming soluble orthophosphate to an insoluble salt. In practice, more complex reactions are taking place including a reduction of the chemical solubility of dissolved greenhouse gases, such as nitrous oxide, present in the wastewater stream. In this respect, it was postulated that phosphorous precipitation will lead to artificial N2 O stripping and hence to an increased carbon footprint of wastewater treatment plants. From lab-scale experiments utilizing N2 O-saturated synthetic sewage solutions, it was evidenced that metal salt addition leads to N2 O stripping with 20.8 g N2 O per liter for a FeCl2 -based precipitant to 26.4 g N2 O per liter for a Aln (OH)m Cl3n-m -based precipitant. Taking this maximum potential stripping effect into account for a carbon footprint analysis, a potential contribution of 16.11 kg CO2, eq ·PE −1 ·a −1 was calculated in a case study, where FeCl3 was considered. With respect to the defined system boundary conditions, the overall on-site and off-site CO2 emissions were raised by 34% from 46.87 kg CO2, eq ·PE −1 ·a −1 to 62.97 kg CO2, eq ·PE −1 ·a −1 through CO2, eq coming from phosphorous precipitation.